Environmental characteristics influences on physical activity among overweight adolescent in urban neighbourhood parks - Danis, Ajau; Sidek, Suriati; Md. Yusof b, Safiah (Elsevier Ltd., 2014)
The link between environmental characteristics of neighborhood park and adolescents’ physical activity is poorly understood. Therefore, present study aims to explore the environmental characteristics of the neighbourhood parks that influence physical activity from the perception of overweight adolescents. Participants were selected using criterion purposive sampling. In-depth semi-structured interviews with 33 overweight adolescents between 13 and 17 years old successfully done. Interviews recorded, transcribed and analyzed based on thematic content analysis. The results showed that physical and social environment influenced physical activity and neighbourhood parks usage. It is essential to consider these environmental characteristics in developing physical activity intervention that aim to promote physical activity among overweight adolescents.